2013
DOI: 10.2478/rrlm-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of GSTM1/GSTT1 null alleles and Ile105Val GSTP1 variant in patients with Nasal Polyposis and hyposmia in a Romanian population group

Abstract: Background. Polymorphisms for genes encoding glutathione S-transferase (GSTM1/GSTT1/GSTP1) might be one of the factors that can influence the variability in susceptibility for 572). Molecular analysis did not reveal an increased frequency for GSTT1 and GSTM1 null alleles in the patients group compared to controls (GSTT1 -95% CI = 0.332 to 1.261, p = 0.192, OR = 0.641, χ2 = 2.120, χ2 = 2.017, OR = 0.321, p = 0.062). Significant statistical differences were found when combined were compared between patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Glutathione S-transferases (GSTs) enzymes, encoded by GST genes, are implicated in detoxification of xenobiotics, and they have a crucial role in protecting tissue from oxidative damage. The variation at the GSTM1 , GSTT1 , and GSTP1 loci has been linked with an increase in the occurrence of cancers, probably due to an increased susceptibility to environmental toxins and carcinogens [ 6 ]. The researchers focused on several polymorphisms of the GST genes: the homozygous deletions of the GSTM1 and GSTT1 genes (the “null genotypes”) and the Ile105Val substitution in the GSTP1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) enzymes, encoded by GST genes, are implicated in detoxification of xenobiotics, and they have a crucial role in protecting tissue from oxidative damage. The variation at the GSTM1 , GSTT1 , and GSTP1 loci has been linked with an increase in the occurrence of cancers, probably due to an increased susceptibility to environmental toxins and carcinogens [ 6 ]. The researchers focused on several polymorphisms of the GST genes: the homozygous deletions of the GSTM1 and GSTT1 genes (the “null genotypes”) and the Ile105Val substitution in the GSTP1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Ozcan et al reported a GSTT1 gene polymorphism for non-allergic nasal polyposis and suggested its importance in the pathogenesis of NP [ 67 ]. On the basis of other research, both GSTM1/GSTT1 null genotypes have been considered to be risk factors for the development of NP and hyposmia (reduced ability to sense odors) in allergic individuals [ 68 ]. The authors thus confirmed the GSTT1 gene polymorphism as a prognostic marker for CRS.…”
Section: From Classical Microbiology To Molecular and Omics Methodsmentioning
confidence: 99%